Can we get along? : an account of communal relationship in bangladesh - Rafi, Mohammad (Dhaka : Pangeree, 2005)
Learning to tolerate different opinions, perspectives, and beliefs is vital to a healthy society. Slim Goodbody's Can't We Get Along? helps students understand the need and importance for tolerance, and the steps they can take to increase peace in their lives and in the world.
A playground fight -- A world of difference -- Country customs -- Regarding religion -- Skin color -- Family structure -- Physical differences -- Likes and dislikes -- Half empty, half full -- Tug of war -- It's natural -- Setting ground rules -- Make your case.
Includes bibliographical references and index.
Lexile: 730.
Keywords: Communal living -- Bangladesh